Existência de solução para um problema envolvendo uma equação diferencial fracionária - Forsch, Fabíola Cristiane (2019)
This paper aims to present results that guarantee the existence of solution to a problem involving a fractional differential equation with antiperiodic boundary conditions. The fractional differential equation considered in such a problem is given in terms of the Caputo fractional derivative. To ensure the validity of the results, we make use of the theory of Leray-Schauder topological degree, and fixed point theorems, namely Altman’s fixed point theorem and Schauder’s fixed point theorem, which are also demonstrated with the aid of properties from the Leray-Schauder topological degree.